Modulating Vascular Hemodynamics With an Alpha Globin Mimetic Peptide (HbαX). Issue 6 (December 2016) - Keller, T.C. Stevenson; Butcher, Joshua T.; Broseghini-Filho, Gilson Brás; Marziano, Corina; DeLalio, Leon J.; Rogers, Stephen; Ning, Bo; Martin, Jennifer N.; Chechova, Sylvia; Cabot, Maya; Shu, Xiahong; Best, Angela K.; et al.
Abstract : The ability of hemoglobin to scavenge the potent vasodilator nitric oxide (NO) in the blood has been well established as a mechanism of vascular tone homeostasis. In endothelial cells, the alpha chain of hemoglobin (hereafter, alpha globin) and endothelial NO synthase form a macromolecular complex, providing a sink for NO directly adjacent to the production source. We have developed an alpha globin mimetic peptide (named HbαX) that displaces endogenous alpha globin and increases bioavailable NO for vasodilation. Here we show that, in vivo, HbαX administration increases capillary oxygenation and blood flow in arterioles acutely and produces a sustained decrease in systolic blood pressure in normal and angiotensin II–induced hypertensive states. HbαX acts with high specificity and affinity to endothelial NO synthase, without toxicity to liver and kidney and no effect on p50 of O2 binding in red blood cells. In human vasculature, HbαX blunts vasoconstrictive response to cumulative doses of phenylephrine, a potent constricting agent. By binding to endothelial NO synthase and displacing endogenous alpha globin, HbαX modulates important metrics of vascular function, increasing vasodilation and flow in the resistance vasculature. Abstract : Supplemental Digital Content is available in the text.